Potential of photoacoustic imaging for assessing tumor perfusion in intraocular tumors and high-resolution choroidal microvascular imaging: from technical advances to clinical translation - Huarong Wu; Cancan Huang; Shu Xu; Yanming Tian (Frontiers in Oncology, 2026)
Accurate diagnosis and treatment-response assessment for intraocular tumors, typified by choroidal melanoma and retinoblastoma, require characterization of tumor microvascular architecture and oxygenation. However, commonly used ophthalmic modalities—such as optical coherence tomography angiography (OCTA), contrast-enhanced ultrasound (CEUS), and magnetic resonance imaging (MRI)—are limited by penetration depth, reduced spatial resolution at depth, and/or insufficient functional specificity, which can hinder noninvasive evaluation of deep hypoxic regions associated with aggressiveness and treatment resistance. Photoacoustic imaging (PAI), which combines optical absorption contrast with ultrasound detection, may help address these gaps under eye-specific safety constraints. Based on a structured literature search and a narrative/scoping synthesis of ophthalmic evidence supported by cross-disciplinary methodological studies, this review summarizes advances and translational considerations of PAI for intraocular tumor assessment. Current evidence—predominantly preclinical and early ophthalmic reports—suggests that PAI may extend vascular visualization beyond the optical scattering limit and enable label-free depiction of intratumoral vascular features in thicker lesions. Multispectral PAI can also be used to estimate three-dimensional oxygenation maps, including apparent oxygen saturation (sO 2 ), although quantification in melanin-rich tumors remains sensitive to optical fluence attenuation and spectral unmixing bias. We discuss multimodal strategies that combine PAI with OCTA, MRI, and positron emission tomography (PET), and highlight key barriers, including standardized sO 2 validation, ocular motion artifacts, and stringent ocular laser safety limits. Overall, PAI is best positioned as a complementary tool rather than a replacement for established ophthalmic imaging, and its clinical value requires rigorous validation.